Novel palmicolous taxa within Pleosporales: multigene phylogeny and taxonomic circumscription - Dhanushka N. Wanasinghe (2018)
© 2018 German Mycological Society and Springer-Verlag GmbH Germany, part of Springer Nature Palm fungi are highly diverse in the tropical regions of Asia. Recent investigations on these palmicolous fungi have led to the collection of astrosphaeriella-like taxa from Calamus, Caryota, and Licuala species in Thailand (Chiang Rai and Narathiwat provinces) and southwest China (Yunnan Province). This study characterizes fungal taxa, which are new to science, based on morphological examination and concatenated DNA sequence data, to infer their familial relationships. Morphological comparisons reveal six new species, viz. Astrosphaeriellopsis caryotae, Fissuroma calami, F. caryotae, Neoastrosphaeriella sribooniensis, Pithomyces caryotae, and P. licualae. Their similarities and differences to other extant species are discussed. The phylogenetic results indicate that all of these new taxa belong to Aigialaceae and Astrosphaeriellaceae (Pleosporales) and support their establishment. Astrosphaeriellopsis is assigned to Astrosphaeriellaceae and the family is amended in order to accommodate both coelomycetous and hyphomycetous asexual morphs. A generic key is presented for Astrosphaeriellaceae to delimit Astrosphaeriella, Astrosphaeriellopsis, Pteridiospora, and Pithomyces. Asexual morph connections of Pithomyces caryotae and P. licualae are established from axenic cultures derived from single ascospores. DNA-based sequence data supports the establishment of our new species; however, the affinities of Astrosphaeriella tornata to other Astrosphaeriella and Pithomyces species are unclear and warrant further investigations with increased taxon sampling.